Oriental rugs an illustrated lexicon of motifs, materials, and origins - Stone, Peter F. (Tuttle Publ., 2013)
This monumental reference work long awaited by collectors and scholars fills an important gap in the available literature on oriental rugs. Lavishly illustrated with over 1000 photographs and drawings, it offers clear and precise definitions for the rug and textile terms in use across a broad swath of the globe from Morocco to Turkey, Persia, the Caucasus region, Central Asia, Afghanistan, Pakistan, India and China